Nightlife and crime: social order and governance in international perspective - Hadfield, Phil (Oxford University Press, 2009)
Nightlife and crime in international perspective / Phil Hadfield -- England and Wales / Phil Hadfield and Fiona Measham -- Scotland / Martin Elvins -- Northern Ireland / Karen McElrath -- Ireland / Mairead Seymour and Paula Mayock -- The Netherlands / Patrick van Calster, Joanne van der Leun, and Ninette van Hasselt -- Norway / Arvid Skutl, Jane Mounteney, and Vibeke Johannessen -- Finland / Marja Holmila and Katariina Warpenius -- Italy / Rosella Selmini and Gian Guido Nobili -- Spain / Anabel RodrIguez Basanta -- Hungary / Zsolt Demetrovics -- Greece / Sophie Vidali -- United States of America / Paul J Gruenewald, Lillian G Remer, and Andrew J Treno -- Canada / Kathryn Graham and Sharon Bernards -- Hong Kong / Karen Joe Laidler -- South Africa / Kopano Ratele, Lu-Anne Swart, and Mohamed Seedat -- New Zealand / Fiona Hutton -- Australia / Tanya Chikritzhs -- Nightlife horizons : some further thoughts and conclusions / Phil Hadfield